Internalisasi Nilai-nilai Pendidikan Islam Multikultural dalam Budaya Masyarakat Lampung Pepadun - Evan Supriyadi; Moh Ali Murtadlo; Rahmat Rahmat (Sekolah Tinggi Ilmu Tarbiyah Bustanul `'Ulum Lampung Tengah, 2023)
Lampung is a multicultural region with a variety of tribes, cultures, customs, languages, and religions. With such diversity, we must tie with a sense of nationalism over the ownership of the Unitary State of the Republic of Indonesia. The purpose of this study is to describe how islamic multicultural education in sakai sambayan culture has been implemented in multicultural societies. In its implementation, qualitative research was used with phenomenological and naturalistic approaches was focused on implementation of islamic multiculturalism education in sakai sambayan culture of the West Tulang Bawang societies. This study concluded that (1) sakai sambayan culture is vital since it can be used as a medium and means of implementation of islamic multicultural education, containing the fundamental beliefs and knowledge sources in harmony with Islamic teachings and (2) sakai sambayan culture has multicultural Islamic educational values, such as unity and solidarity, mutual respect and tolerance, work together, and keeping of social relationship and social harmony among Lampung societies. This research has implications for developing the Islamic multicultural education in West Tulang Bawang regency as a region of multicultural.